Changes in the structure of income and consumption in Lithuania - Pukelienë V. (Selected readings on economies in transition, 2000)
Lithuania gained its independence in 1990. In the middle of 1993, the decrease in real wages was halted, with the rate of price increases and average wages becoming almost equal after the three-year period. The real income decrease stopped in the second half of 1993 and the increase in real income was 4 percent in 1993. Average cash income per household member has been increasing. Average monthly official income per household member at the end of 1993 was 40,2 USD per month (482,4 USD annually) and 66,28 USD per month or 795,36 USD over the year at the end of 1995. During this period, real household income has increased insignificantly and by the end of 1995, it amounted to just under 40 per cent of the December 1990 level in urban areas and it was even less in rural areas. The consumption and income structure in Lithuania during the years 1989 - 1995 is examined in this paper.